Diagnostic Accuracy of FNAC in Tuberculous Cervical Lymphadenitis- Experience from a Tertiary Care Centre - Zeba Ahmed; Muhammad Khalid; Zille Huma; Reema Mirza; Sana Mehfooz; Nataliya Raja (KARACHI MEDICAL AND DENTAL COLLEGE, 2024)
Objective: To analyze the role of Fine Needle Aspiration Cytology (FNAC) in the detection of tubercu- lous cervical lymphadenitis. Methods: A retrospective cross-sectional study was carried out at the Dr. Ruth K. M. Pfau Civil Hospi- tal Karachi's ENT-Head and neck surgery department, from April 2021 till March 2022. Patients with ages between 30-70 years having cervical lymphadenopathy lasting for more than or equal to 3 months and having 1 or more palpable lymph nodes of more than or equal to 1 cm were included in the study. A questionnaire was designed for data collection from the patients. The names, ages, gen- der of the patients, the duration of disease noted down. The dominating nodes' FNAC and ultrasound neck were done. Inconclusive FNAC were followed by excisional biopsy. The sample size was taken as 50, with analysis done through SPSS version 23. Results: There were 34 (64%) females and 16 (32%) males present. The patients' average age was 52.94 ± 9.43 years; 33 patients were below the age of 55, out of which 25 (75.7%) had positive and 8 (24.2%) had negative FNAC. Of the patients over the age of 55, 11 (64.7%) had positive and 6 (54.5%) had negative FNAC. The illness lasted 5.84 ± 2.63 months on average, 2 months being the minimum duration of disease, while maximum duration was 15 months. The duration of less than or equal to six months was observed in 40 (80%) and the duration of more than 6 months was ob- served in 10 (20%) of patients. With a mean size of 2.5 ± 1.14 cm, 29 patients (58%) had unilateral nodes and 21 (42%) had bilateral nodes. FNAC has a sensitivity of 97% and specificity of 72.2%, meaning that it was positive in 36 individuals and negative in 14. Conclusion: FNAC plays a significant role in the diagnosis of tuberculous cervical lymphadenitis.